2019
DOI: 10.2147/jep.s218261
|View full text |Cite
|
Sign up to set email alerts
|

<p>In vitro anticoagulant effect of <em>Crassocephalum crepidioides</em> leaf methanol extract and fractions on human blood</p>

Abstract: Background Blood coagulation is a rapid and efficient process that produces clot formation which requires regulation. A derangement of blood coagulation is a feature of many disease conditions. This study investigated the in vitro effects of Crassocephalum crepidioides Benth S. Moore leaf methanol (crude) extract and its partitioned solvent fractions on blood coagulation of Healthy human volunteers. Methods The secondary metabolites from dried… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Compounds identified from the GC-MS analysis of the hexane fraction of C. crepidioides leaves with possible anticoagulant activities have been earlier reported [29]. Some of the identified bioactive compounds that may be responsible for observed activities in the present study include eugenol and α-linolenic acid (S/N 6 & 13) with antiaggregant activity; thujone (S/N 5) with antiplatelet activity; coumarin-related compounds, benzofuran and benzofuranone (S/N 4 & 7); α-linolenic acid (S/N 13) which possesses antiaggregant activity; n-hexadecanoic acid and its methyl ester (S/N 8&9) which are known to possess lipid-lowering activities (Table 3).…”
Section: Gc-ms Phytochemical Characterizationmentioning
confidence: 79%
See 1 more Smart Citation
“…Compounds identified from the GC-MS analysis of the hexane fraction of C. crepidioides leaves with possible anticoagulant activities have been earlier reported [29]. Some of the identified bioactive compounds that may be responsible for observed activities in the present study include eugenol and α-linolenic acid (S/N 6 & 13) with antiaggregant activity; thujone (S/N 5) with antiplatelet activity; coumarin-related compounds, benzofuran and benzofuranone (S/N 4 & 7); α-linolenic acid (S/N 13) which possesses antiaggregant activity; n-hexadecanoic acid and its methyl ester (S/N 8&9) which are known to possess lipid-lowering activities (Table 3).…”
Section: Gc-ms Phytochemical Characterizationmentioning
confidence: 79%
“…e PT is a coagulation parameter used in evaluating the tissue factor pathway and thus the activities of the factors of the extrinsic coagulation pathway, while the aPTT determines the activities of factors involved the contact (intrinsic) and the common pathways. e PT and aPTT are standard tests for monitoring coumarin and heparin therapies, respectively [29,44]. e observed prolongation of both the PT and aPTT in experimental rats after C. crepidioides administration suggests a reduction in activities or inhibition of factors V, X, II of the common coagulation pathway.…”
Section: Discussionmentioning
confidence: 99%
“…[14,15] Recent studies have also noted that coumarins have multiple biological activities, such as antitumoral, anticoagulant, anti-inflammatory, antimicrobial and antioxidant activities. [16][17][18][19] The volatiles in CGT fruits not only exert antibacterial, antiinflammatory and expectorant functions but also play an important role in the quality control of the crude drug. [20] Xie et al extracted 56 volatile compounds from the peels of CGT fruits by headspace solid-phase microextraction (HS-SPME) and compared the compounds with the extracts from steam distillation and solvent extraction, and the results obtained by HS-SPME showed satisfactory repeatability.…”
Section: Introductionmentioning
confidence: 99%
“…Alpha-linolenic acid has been reported to act as an antiaggregant, Eugenol was reported as an anticoagulant agent in Cinnamomum cassia (Kim et al, 2010), while thujone and flavonoids have also been reported to inhibit platelet aggregation (Formica and Regelson, 1995;Cordier and Steekamp, 2011). Ayodele et al (2019) similarly reported Thujone, Eugenol, α-linolenic acid, and coumarin-related compounds; Benzofuran, Benzofuranone and Benzene acetaldehyde as possible anticoagulant agents in C. crepidioides leaf methanol extract and fractions.…”
Section: Discussionmentioning
confidence: 79%
“…The antioxidant, cytoprotective (Odukoya et al, 2007;Wijaya et al, 2011), cancer chemoprotective and anti-tumor activities (Chia-chung et al, 2007;Chaitanya et al, 2013) of the plant have also been demonstrated. The in vitro anticoagulant activity of the plant leaf methanol extract and fractions was recently reported (Ayodele et al, 2019). Therefore, with such great medicinal value being suggested, a detailed analysis to identify and characterize the phytochemical compounds in the plant is very much needed.…”
Section: Introductionmentioning
confidence: 99%